2014
DOI: 10.5505/adlitip.98700
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination for using hand and wrist measurements in Turkish population.

Abstract: . Sex determination by using hand and wrist measurements in Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…In discriminant functions where more than one variable was used, the most accurate binary model for sex differentiation was hand length and wrist width at 86.6%. 5 Another study reported accuracy of 77% in males and 80% in females when right hand length was used in sex differentiation, compared to 79% accuracy in males and 81% in females when left hand length values were used. Right hand width revealed sexual dimorphism with 80% accuracy in males and 83% accuracy in females and left-hand width with 81% accuracy in males and 82% accuracy in females.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In discriminant functions where more than one variable was used, the most accurate binary model for sex differentiation was hand length and wrist width at 86.6%. 5 Another study reported accuracy of 77% in males and 80% in females when right hand length was used in sex differentiation, compared to 79% accuracy in males and 81% in females when left hand length values were used. Right hand width revealed sexual dimorphism with 80% accuracy in males and 83% accuracy in females and left-hand width with 81% accuracy in males and 82% accuracy in females.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measurements from the individual's dominant hand have been described as eliciting more objective results, and right-side measurements have been adopted in studies. 5 However, we evaluated both the right and left upper extremities in sex estimation in this study. We think it is necessary and useful for anthropometric measurements performed in consideration of the probability of both extremities being present in forensic cases and for models developed from these measurements to be considered from a broader perspective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations